STREPTOCOCCAL THROAT INFECTION AMONG YEMENI CHILDREN - Saleh, Madha (Iraqi Journal of Science, 2024)
This package was conducted in Taiz/ Yemen as cross sectional study and mainly aimed to determine the prevalence rate of Group Aβ- herrolyhc streptococcus among school age children cases (1-15years) with pharyngitis and/ or tonsillitis. GAβHS was found in 28.6% out of the total 475 throat swab specimens, which were taken from cases with clinical sore throat. A peak of GAβHS bacterial isolates was noticed in the 6-10 years age group. The gender was found of no value as a risk factor in increasing or decreasing the prevalence rate of infection. Other risk factors were found variable in their influence as the family size, which was of high significant effect on the prevalence rate of GAβHS infection, and the seasonal variation as it was found that the highest prevalence rates at winter season (November and December) as well as rainy season (July and August). No association was pointed out between the GAβHS isolates and the results of anti-streptolysin. Antimicrobial sensitivity test revealed that amoxicillin was the antibiotic of choice for the presumptive treatment of GAβHS sore throat as 94.3% of the isolates were sensitive for this antibiotic.